Does the Semi-Autonomous Agency Model Function in a Low-Governance Environment? The Case of the Road Development Agency in Zambia - Raballand, Gael (World Bank, Washington, DC, 2013)
This paper uses Zambia as a case study to assess empirically whether political interference in a low-governance environment has diminished in the past years as expected after a semi-autonomous agency model was set up ten years ago. The road sector in Zambia has experienced some significant developments since then. The paper uses data on contract from 2008 to 2011 and analyses a number of key trends related to Road Development Agency governance and staffing dynamics as well as procurement and project selection within the institution. The main findings indicate that, after some years of implementation of these reforms, there is reason to question whether the model of semi-autonomous agency enables road management to be shielded from political interference. Zambia may be an isolated case but, so far, this model does not seem to have been able to decrease political interference in the selection or supervision of projects and there seems to have been an increased lack of accountability of civil servants working in this sector.